The impact of supply chain quality integration on green supply chain management and environmental performance. (4th July 2019) - Yu, Yubing; Zhang, Min; Huo, Baofeng
Abstract : This study develops a model to investigate the relationships between supply chain quality integration (SCQI) (supplier quality integration and customer quality integration), green supply chain management (GSCM) (green purchasing and customer green cooperation) and environmental performance. The model is empirically tested using data collected from 308 manufacturing companies in China. We find that supplier and customer quality integration have positive impact on green purchasing and customer green cooperation, which improve environmental performance. Supplier and customer quality integration also influence environmental performance indirectly through green purchasing and customer green cooperation. The results provide insights into the mechanisms through which SCQI influences environmental performance, and clarify the complex relationships between SCQI and GSCM, contributing to the quality management and green management literature and practices.